Existence of Solutions for a Schrödinger–Poisson System with Critical Nonlocal Term and General Nonlinearity. (28th August 2020) - Zhang, Jiafeng; Guo, Wei; Chu, Changmu; Suo, Hongmin
Abstract : We study the existence and multiplicity of nontrivial solutions for a Schrödinger–Poisson system involving critical nonlocal term and general nonlinearity. Based on the variational method and analysis technique, we obtain the existence of two nontrivial solutions for this system.